Age, familiarity, and intuitive use: An empirical investigation. (January 2019) - Lawry, Simon; Popovic, Vesna; Blackler, Alethea; Thompson, Helen
Abstract: Research has shown that older adults interact with products less intuitively than younger adults, and that familiarity is an essential element of intuitive interaction. This paper reports on the findings of two empirical studies that examined familiarity in younger and older adults. Each study comprised 32 participants over four age groups. The first study required participants to use their own contemporary products in their homes in order to investigate older adults' familiarity with them, and how this familiarity differed from that of younger adults. Older people were less familiar with their own contemporary products that younger people. The second study aimed to investigate differences in familiarity between younger and older adults while using products that they did not own and were likely to be less familiar with. When using products not already familiar to them, both middle aged and older adults showed significantly lower familiarity than younger people. The significance of this research is in its empirical findings about familiarity differences between age groups. It has been recognised that the identification and understanding of differences in familiarity will enable designers to design more intuitive interfaces and systems for both younger and older cohorts. The implications of the findings from the two studies reported here are discussed in light of this recognition. Highlights: Older adults interact with products less intuitively than younger adults. Familiarity is an essential element of intuitive interaction. Study one indicated that older adults (over 60) were less familiar with their own products than younger adults. Older (over 60) and middle-aged adults (over 45) were less familiar with products they did not own than those under 45. Older people were faster at using an analogue product, and younger people were faster with the digital equivalent.